Synthesis Applied 4th-Order Constant Absolute Bandwidth Frequency-Agile Bandpass Filter With Cross-Coupling - Dengyao Tian; Quanyuan Feng; Qianyin Xiang (IEEE Access, 2018)
A novel 4th-order cross-coupled electrical tunable bandpass filter with constant absolute bandwidth and high frequency selectivity is proposed. The electric coupling coefficients and the magnetic coupling coefficients of the cross-coupled resonators and the external quality factor of the tunable filter are investigated. The design curves of coupling coefficients and external quality factor versus the resonant frequency are synthesized for the cross-coupled tunable filter. Tunable resonator with separate electric dominant and magnetic dominant coupling regions is designed to build the cross-coupled tunable filter topology. Theoretical analysis is derived to estimate the coupling coefficients and the performance of the proposed filter. A prototype is fabricated and measured. The measurement shows that the filter has a −3 dB bandwidth of 117 ± 3MHz from 0.95 to 1.48 GHz. Two cross-coupled transmission zeros beside the passband are generated, and the frequency selectivity is enhanced. The −30 dB/−3 dB bandwidth shape factor is 1.83~1.93.